Results from an evaluation of tobacco control policies at the 2010 Shanghai World Expo. (25th May 2013) - Li, Xiang; Zheng, PinPin; Fu, Hua; Berg, Carla; Kegler, Michelle
Abstract : Background: Large-scale international events such as World Expos and Olympic Games have the potential to strengthen smoke-free norms globally. The Shanghai 2010 World Expo was one of the first large-scale events to implement and evaluate the adoption of strict tobacco control policies. Objective: To evaluate implementation of tobacco control policies at the 2010 World Expo in Shanghai, China. Methods: This mixed methods evaluation was conducted from July to October 2010. Observations were conducted in all 155 pavilions and outdoor queuing areas, all 45 souvenir shops, a random sample of restaurants (51 of 119) and selected outdoor non-smoking areas in all sections of the Expo. In addition, intercept surveys were completed with 3022 visitors over a 4-month period. Results: All pavilions and souvenir shops were smoke-free. Restaurants were smoke-free, with only 0.1% of customers observed smoking. Smoking was more common in outdoor non-smoking areas, but still relatively rare overall with only 4.5% of visitors observed smoking. Tobacco products were not sold or marketed in any public settings except for three pavilions that had special exemptions from the policy. Overall, 80.3% of visitors were aware of the smoke-free policy at the World Expo, 92.5% of visitors supported the policy and 97.1% of visitors were satisfied with the smoke-free environment. Conclusions: Tobacco control policies at the World Expo sites were generally well-enforced and accepted although compliance was not 100%, particularly in outdoor non-smoking areas.